2018
DOI: 10.1097/md.0000000000011809
|View full text |Cite
|
Sign up to set email alerts
|

Survey of family satisfaction with intensive care units

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 25 publications
5
27
3
5
Order By: Relevance
“…Both ICUs had waiting/family rooms and family members assessed their satisfaction with the atmosphere in them as being considerably lower than for the other items of the FS-Care subscale. Similar findings have been reported in prior studies where the FS-ICU 24 questionnaire was used [43,45,46]. Engström and Söderberg [13] reported that family members greatly appreciated this room as it gave them the opportunity to step back while remaining close to the ICU patient.…”
Section: Family Satisfaction In the Icu The Fs-care Subscalesupporting
confidence: 79%
“…Both ICUs had waiting/family rooms and family members assessed their satisfaction with the atmosphere in them as being considerably lower than for the other items of the FS-Care subscale. Similar findings have been reported in prior studies where the FS-ICU 24 questionnaire was used [43,45,46]. Engström and Söderberg [13] reported that family members greatly appreciated this room as it gave them the opportunity to step back while remaining close to the ICU patient.…”
Section: Family Satisfaction In the Icu The Fs-care Subscalesupporting
confidence: 79%
“…Previous studies had found that the waiting room setting satisfaction to be either poor or moderate (1,3,4,9,12,23). Heyland et al (1) reported that the lowest satisfaction scores belonged to the waiting room; however, improvement of waiting room conditions did not improve the satisfaction results.…”
Section: Discussionmentioning
confidence: 95%
“…In the study of Olabisi et al (2020), age, income and the level of education significantly influenced the level of anxiety. However, several studies found that there were no significant relationships between family satisfaction and demographic characteristics such as age or gender (Haave et al, 2021; McLennan & Aggar, 2020; Min et al, 2018). It is thought that the demographic characteristics of family members could be considered to plan initiatives to reduce their anxiety levels, increase their satisfaction with the ICU and enhance their perception of social support.…”
Section: Discussionmentioning
confidence: 99%